2017
DOI: 10.1182/blood-2016-09-737981
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus in asymptomatic blood donors in Martinique

Abstract: study of the platelet inhibitor prasugrel in children with sickle cell disease was designed to identify drug doses that inhibit platelet function between 30% and 50%, a level thought to balance safety and efficacy, 24 similar to the level of inhibition observed here, although the dual effects of RN-1 on platelet function and platelet counts could pose an additional risk for bleeding that will require further monitoring.Our results show that administration of RN-1 to normal baboons over a prolonged period incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 16 publications
12
101
3
Order By: Relevance
“…40,41 The measured mean genomic titers of inactivated ZIKV in this study were higher than the RNA loads found in ZIKV RNA-reactive, asymptomatic blood donors in French Polynesia during 2013 through 2014 (mean, 4.85 log 10 GEq/mL; range, 3.4-6.9 log 10 GEq/mL), as determined using the same PCR methodology, 28 and in Martinique in 2016 (range, 2.09-6.50 log 10 GEq/mL) using a comparable methodology. 42 This indicates that, if the amotosalen/UVA method had been in routine use, it may…”
Section: Discussionmentioning
confidence: 99%
“…40,41 The measured mean genomic titers of inactivated ZIKV in this study were higher than the RNA loads found in ZIKV RNA-reactive, asymptomatic blood donors in French Polynesia during 2013 through 2014 (mean, 4.85 log 10 GEq/mL; range, 3.4-6.9 log 10 GEq/mL), as determined using the same PCR methodology, 28 and in Martinique in 2016 (range, 2.09-6.50 log 10 GEq/mL) using a comparable methodology. 42 This indicates that, if the amotosalen/UVA method had been in routine use, it may…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of ZIKV transmission was implemented probabilistically for each mosquito bite when the infectious case was symptomatic. Recent evaluation suggests that symptomatic cases reached levels of molecular viral load that were significantly higher than asymptomatic cases 37 . Although this level depends on the time of sampling, it may be an indication of lower transmissibility of asymptomatic infection.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, an estimated 80% of ZIKV infections do not develop symptoms and symptomatic infection includes a pre-symptomatic viraemic period [102,105,[156][157][158][159][160], although the viraemic period appears to be typically brief with relatively low levels of virus [102,105,161,162]. In addition, ZIKV RNA has been detected in asymptomatic blood donors during outbreaks in French Polynesian (2013-14) [105,163], Puerto Rico (April 3-June 11, 2016) [164], Martinique (January to June 2016) [165] and the continental US (May to October, 2016) [166]. Thirdly, there is a general consensus that ZIKV is the causative agent of severe neurological disorders [43,[167][168][169][170][171] including microcephaly in newborns [95,96,[172][173][174][175] and Guillain-Barré syndrome (GBS) in the wider population [109,[176][177][178][179].…”
Section: Why Zikv Represents a Potential Threat To Blood Safetymentioning
confidence: 99%